An overview of mortgage enforcement in Malaysia / Siti Dalila Abdul Ghani … [et al.] - Abdul Ghani, Siti Dalila; Mohd Nazri, Farah Nur Ain; Mohd Hakimi, Nur Izzah Najihah; Ibrahim, Safurah (2023)
Title: “An Overview of Mortgage Enforcement in Malaysia”